Phosphorus/nitrogen co-doped and bimetallic MOF-derived cathode for all-solid-state rechargeable zinc–air batteries. Issue 55 (10th September 2020) - Yang, Xing; Wu, Xianghua; Guo, Zeping; Li, Qingyu; Wang, Hongqiang; Ke, Chujun; Zeng, Wei; Qiu, Xiafei; He, Yun; Liang, Xiaoguang; Kim, Yoonseob
Abstract : The bimetallic FeNi-MOFs are employed to fabricate P–FeNi and N–carbon co-doped bifunctional catalyst. Due to the enhanced catalytic performance, the peak power density of all-solid-state zinc–air battery is 159 mW cm −2 . Abstract : With the merits of high safety and energy density, all-solid-state zinc–air batteries possess potential applications in flexible and wearable electronic devices. Especially, the air cathodes with bifunctional catalytic activity, i.e. oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) have been received enormous attention. In this work, we provide a novel phosphorus/nitrogen co-doped and bimetallic metal–organic framework (MOF)-derived cathode configurated with phosphorus-doped bimetallic FeNi alloys and a nitrogen-doped porous carbon layer loaded on graphene (P–FeNi/NC@G). The P–FeNi/NC@G electrode exhibits a superior OER activity with an overpotential of 310 mV at 10 mA cm −2 and an ORR performance with a half-wave potential of 0.81 V. With P–FeNi/NC@G as the air cathode, the integrated all-solid-state rechargeable zinc–air battery presents a high open-circuit voltage of 1.53 V, a high peak power density of 159 mW cm −2, a small charge–discharge voltage gap of 0.73 V at 5 mA cm −2, as well as excellent long-term stability up to 144 cycles. This work not only expands the air cathode materials database but also develops a new co-doped synthesis method that can be utilized to fabricate a cathode with promoted catalytic efficiency, resulting in improved performance for an all-solid-state zinc–air battery.